Phage therapy in aquaculture : use of phage cocktails and lysozyme - Mateus, Lília Cristiana da Silva (2018)
Aquaculture is one of the fastest growing food industry sectors in the world in recent years. However, the appearance of pathogenic microorganisms, including multirresistant bacteria, and their dissemination in the environment has become a problem for the aquaculture industry. This means that it is necessary to develop less harmful strategies to the environment to allow a sustainable growth of the aquaculture systems. Phage therapy emerges as a potential alternative to inactivate pathogenic bacteria in aquaculture. The main objective of this study was to assess the efficacy of phage therapy to inactivate fish pathogenic bacteria. The use of phage cocktails and lysozyme was also evaluated on the efficiency of phage therapy. The phage therapy assays were performed with the bacterium Vibrio parahaemolyticus and with three phages produced on this bacterium (VP-1, VP-2 and VP-3). The dynamics of phage-bacteria interaction was characterized in Tryptic Soy Broth through host and phage quantification, respectively by pour plate and by the double-layer agar technique. The three phages were tested alone and in cocktails of two or three phages. The efficiency of the bacterial inactivation by the phages was tested at different lysozyme concentrations (range 0.8 μg mL-1 to 20 mg mL-1). As the selection of bacteriophages is a key factor for the success of phage therapy, the host range, their survival in aquaculture water, as well as the burst size and the explosion time, were determined. The cross-infection was used to determine the phage host range. To determine the survival of the phages in marine water, the double-layer agar technique was used. The burst size and the explosion time were calculated by the one-step growth curve analysis. The use of cocktails of two and three phages was significantly more effective (reduction of 4 log at 2 h of treatment) than the use of the VP-1, VP-2 and VP-3 phages alone (reductions of about 0.6, 0.8 and 2.6 log, at 2 h of treatment respectively for the VP-1, VP-2, and VP-3 phages). The combination of phage plus lysozyme showed a better inhibitory activity when compared with the activity of the phage alone. The VP-1 and VP-2 phages were more efficient to inactivate the Vibrio (reduction of about 4 log after 6 - 8 h treatment), in the presence of high concentrations of lysozyme, than the VP-3 phage. However, the VP-3 phage was more efficient in the presence of low concentrations of lysozyme (reduction of 3.2 log after 2 h of incubation). The results of the cross-infection showed that the phages of Vibrio parahaemolyticus also infect Vibrio anguillarum and Aeromonas salmonicida with high efficiency. The assays of phage survival in aquaculture water showed that the phages remain viable for long time periods (more than 5 - 7 months). The VP-3 phage presented a higher burst size and a shorter latent period (42 and 40 min, respectively) than the other two phages (9 and 15 and 120 min and 90 min, respectively, for the VP-1 and VP-2 phages). In conclusion, the use of phage cocktails appears to be an effective approach to treat vibriosis. Bacterial inactivation is more efficient and occurs earlier when the phage cocktails are used, but their use in vitro does not prevent bacterial regrowth after treatment. However, the use of phage cocktails retarded the regrowth of the bacteria. The application of phages with lysozyme to eliminate or reduce fish pathogenic bacteria in aquaculture can be a promising strategy, namely when less effective phages are available. Besides, the use of phages with a high burst size and a short latent period clearly increase the efficiency of phage therapy.